2002
DOI: 10.2320/matertrans.43.3078
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Orthodontic Wires According to Heat Treatment Conditions

Abstract: Heat treatments are applied to orthodontic wires in order to relieve the stresses arising during orthodontic work. Four types of wires were heated in air, argon or vacuum environments, and cooled in the furnace or in a water bath. The susceptibility to corrosion and mechanical properties of the heat-treated wires were investigated. Heat treatment marginally increased the yield strength and elastic modulus of all wires. After heat treatment in air, both water-and furnace-cooled wires had similar low corrosion r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, it is unlikely that the TiN layer mainly leads to these results, because it is a thin layer. Several studies have reported that mechanical properties of SS and Ni-Ti wires are changed by heating treatment [18][19][20][21] . In this study, orthodontic wires were heated at 220°C for 7 min for TiN coating.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unlikely that the TiN layer mainly leads to these results, because it is a thin layer. Several studies have reported that mechanical properties of SS and Ni-Ti wires are changed by heating treatment [18][19][20][21] . In this study, orthodontic wires were heated at 220°C for 7 min for TiN coating.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the corrosion properties of the samples, potentiodynamic testing was performed on 1cm_long samples in sea water(3.5%NaCl)at room temperature, using a potentiostat(model solartron SI 1287).Samples for corrosion testing were cleaned and rinsed in distilled water, and dried, Oh et al (2002). The potential scanning rate was 0.5mV/s, the scanning rang was -800mV_500mV, platinum auxiliary electrode, and a saturated calomel electrode (SCE) was used as the reference electrode.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the anticorrosive behavior of Ni-Ti-based wires has been evaluated in several works 5,[7][8][9][10] , which presented different results, in the great majority of the cases. Kim and Johnson 7 analyzed the breakdown potential of stainless steel, Ni-Ti, and titanium orthodontic wires in 0.9% m/v NaCl.…”
Section: Introductionmentioning
confidence: 99%